2017
DOI: 10.1002/2017ja024637
|View full text |Cite
|
Sign up to set email alerts
|

The Storm Time Evolution of the Ionospheric Disturbance Plasma Drifts

Abstract: In this paper, we use the C/NOFS and ROCSAT‐1 satellites observations to analyze the storm time evolution of the disturbance plasma drifts in a 24 h local time scale during three magnetic storms driven by long‐lasting southward IMF Bz. The disturbance plasma drifts during the three storms present some common features in the periods dominated by the disturbance dynamo. The newly formed disturbance plasma drifts are upward and westward at night, and downward and eastward during daytime. Further, the disturbance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 36 publications
(61 reference statements)
2
34
0
Order By: Relevance
“…The ionospheric currents show the diverse patterns during the present three cases. Rastogi et al (), Xiong et al (), and Zhang, Liu, Le, Chen, and Kuai () showed that the flares induce the eastward EEJ to enhance, according with the result during X8.2 flare on 10 September. Rastogi et al (, ) and Sripathi et al () found that solar flares produce a westward increase under a counter EEJ, which is consistent with the result that the westward EEJ is increased on 6 September flare.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The ionospheric currents show the diverse patterns during the present three cases. Rastogi et al (), Xiong et al (), and Zhang, Liu, Le, Chen, and Kuai () showed that the flares induce the eastward EEJ to enhance, according with the result during X8.2 flare on 10 September. Rastogi et al (, ) and Sripathi et al () found that solar flares produce a westward increase under a counter EEJ, which is consistent with the result that the westward EEJ is increased on 6 September flare.…”
Section: Discussionmentioning
confidence: 94%
“…Geomagnetic storms are known to affect the ionospheric electrodynamics due to two types of sources, the penetration electric field from high to low latitudes (e.g., Kelley et al, 2003;Kikuchi et al, 1978) and disturbance dynamo electric field (DDEF) result from the storm-time changes in neutral winds (e.g., Blanc & Richmond, 1980;Zhang, Liu, Le, Chen, & Kuai, 2017). The penetration electric field happens mainly when the interplanetary magnetic field (IMF) Bz abruptly turns southward.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiong et al () found that the peak of the disturbance winds can corotate from 2300 to 0300 local time (LT) as they propagate from high to middle and low latitudes. Zhang et al () further provided observations that the DDEF could also be shifted to later local times. Hairston et al () showed a persistent enhanced downward plasma vertical drift at dayside and early evening hours through all phases of the 26 September 2011 storm, suggesting a total absence of the prompt penetration electric field.…”
Section: Introductionmentioning
confidence: 97%
“…Geomagnetic storms are known to affect the field‐perpendicular plasma drifts due to the electric field penetrated from high to low latitudes (e.g., Kelley et al, ; Kikuchi et al, ) and disturbance dynamo electric field due to the storm time changes in neutral wind (e.g., Blanc & Richmond, ; Zhang et al, ). While penetration of electric field happens mainly during the main phase of geomagnetic storms, the disturbance dynamo electric field starts developing about 3–4 hr after the storm onset because of the time taken by the disturbance neutral wind to travel from high to low latitudes (e.g., Fujiwara et al, ; Huang et al, ; Xiong et al, ).…”
Section: Introductionmentioning
confidence: 99%